2017
DOI: 10.1007/s10014-017-0303-y
|View full text |Cite
|
Sign up to set email alerts
|

Enchondromatosis-associated oligodendroglioma: case report and literature review

Abstract: Enchondromatosis is a rare skeletal disorder characterized by the development of multiple enchondromas, which can also manifest non-cartilage tumors including gliomas. Here, we describe a genetic analysis of a low-grade glioma that developed in an enchondromatosis case. A 32-year-old man with a long history of enchondromatosis developed a left frontal tumor. The histopathological findings of his surgical specimen revealed characteristics of a low-grade glioma with an IDH1 c.395G>A (R132H) mutation and 1p/19q c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…(2016) [ 14 ] 55/F Left frontal, temporal and parietal lobes Anaplastic astrocytoma 22 Achiha et al. (2017) [ 15 ] 32/M Left frontal lobe Oligodendroglioma 23 Current case …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2016) [ 14 ] 55/F Left frontal, temporal and parietal lobes Anaplastic astrocytoma 22 Achiha et al. (2017) [ 15 ] 32/M Left frontal lobe Oligodendroglioma 23 Current case …”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, three more cases were published by other authors, and three of these lesions were in the frontal lobe [ 13 15 ]. The fourth case (our current patient) has a brainstem lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Enchondromatosis including Ollier disease and Maffucci syndrome are caused by somatic mutations of IDH-1 or 2, and therefore can be associated with Central nervous system gliomas. Achiha et al [5] described an adult patient with enchondromatosis and oligodendroglioma (IDH-1 mutant and 1p/19q co-deleted), who was tumor free for more than 18 months. [5] Similarly, Amlashi et al [6] have observed better outcomes for syndromic medulloblastomas, whereas Huttner et al [7] found increased survival in children with GBM and type-1 neurofibromatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Ollier disease can occur with other mesenchymal tumors, such as angiosarcomas, osteosarcomas, and thyroid adenomas, or with non-mesenchymal tumors, such as leukemia [ 3 ], ovarian carcinoma [ 4 ], and central nervous system gliomas [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. The prevalence of malignancies in OD is about 53% [ 28 ], whereas that of sarcomatous degeneration of enchondromas ranges from 20 to 50% [ 1 , 10 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature review disclosed only 30 cases of gliomas associated with Ollier disease [ 5 , 6 , 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 30 ], most of them belonging to the pre-molecular era.…”
Section: Introductionmentioning
confidence: 99%